2018
DOI: 10.3389/fimmu.2018.03019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Piecemeal Degranulation and Vesicular Transport of MBP-1 in Liver-Infiltrating Mouse Eosinophils During Acute Experimental Schistosoma mansoni Infection

Abstract: Eosinophils have been long associated with helminthic infections, although their functions in these diseases remain unclear. During schistosomiasis caused by the trematode Schistosoma mansoni, eosinophils are specifically recruited and migrate to sites of granulomatous responses where they degranulate. However, little is known about the mechanisms of eosinophil secretion during this disease. Here, we investigated the degranulation patterns, including the cellular mechanisms of major basic protein-1 (MBP-1) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…First, we identified eosinophils during F. hepatica infection and showed that they augment with the time of infection, a feature that also characterizes infections by B. malayi ( 23 ), N. brasiliensis ( 24 ), A. cantonensis ( 25 , 26 ). In line with our results, eosinophils constitute 40–60% of the cells in the peritoneal cavity of B. malayi or S. mansoni -infected mice ( 23 , 30 ). The parasite itself could promote the accumulation of greater number of eosinophils in the peritoneal cavity after invading the intestinal wall that allows the juvenile flukes to reach the peritoneal cavity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, we identified eosinophils during F. hepatica infection and showed that they augment with the time of infection, a feature that also characterizes infections by B. malayi ( 23 ), N. brasiliensis ( 24 ), A. cantonensis ( 25 , 26 ). In line with our results, eosinophils constitute 40–60% of the cells in the peritoneal cavity of B. malayi or S. mansoni -infected mice ( 23 , 30 ). The parasite itself could promote the accumulation of greater number of eosinophils in the peritoneal cavity after invading the intestinal wall that allows the juvenile flukes to reach the peritoneal cavity.…”
Section: Discussionsupporting
confidence: 91%
“…However, their role during infection is rather controversial. Experimental infections either with the nematodes Brugia malayi ( 23 ), Nippostrongylus brasiliensis ( 24 ), Angiostrongylus cantonensis ( 25 , 26 ), Heligmosomoides polygyrus ( 19 ), Trichinella spiralis ( 27 ), Strongyloides ratti ( 28 ), Trichuris muris ( 29 ), or the trematode Schistosoma mansoni ( 30 ) are characterized by strong eosinophilia. However, only in the case of B. malayi or N. brasiliensis infections, eosinophils seem to mediate unquestionable host protection by reducing damage caused by the parasite ( 17 , 31 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the eosinophil response to S mansoni eggs is much more pronounced than that of neutrophils, the principal role of eosinophils during schistosomiasis is still not fully understood. It remains uncertain whether they act as major effector cells against the worms, or mediators in tissue homeostasis favouring the establishment of the parasites, or merely as facilitators of tissue remodelling and debris clearance during infection 65 . However, in vitro experiments clearly demonstrated that eosinophil activation can occur through antibody‐dependent cytotoxicity to exert damage on S mansoni parasites 66,67 and that degranulation products such as Major Basic Protein‐1 (MBP‐1) are primary eosinophil mediators in this activity 65 …”
Section: Composition Of the Granulomamentioning
confidence: 99%
“…The lack of response may be due to the low expression of PD-L1 by a malignant cell clone and/or tumor microenvironment cells in most types of NHL and MM 11 14 , unlike HL 9 , 15 . Simultaneously, TIM-3 is considered a perspective target for therapeutic monoclonal antibodies, particularly in combination 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%